Lipase-Catalyzed Dynamic Combinatorial Resolution and the Synthesis of Heteroaromatic Cyanohydrin Ester Enantiomers - Sundell R; Turcu MC; Kanerva LT (BENTHAM SCIENCE PUBL LTD, 2022)
Five structurally related thiophene-based aldehydes, acetone cyanohydrin, a base, a lipase enzyme and isopropenyl acetate have been mixed in one-pot, leading to the dynamic combinatorial resolution of a cyanohydrin library. The process is applied in optimizing synthetic conditions for the cyanohydrin acetate library obtained in terms of reactivity and enantiopurity. Anhydrous Na2CO3 and lipase PS-D (Burkholderia cepacia lipase) or Novozym 435 (Candida antarctica lipase B) preparations are shown to be the best catalyst combinations for the DCR of the substrate series in toluene. The justification of the optimized process is confirmed by preparing the thiophene -based (R)-cyanohydrin acetates with 68-99% isolated yields and 82-91 % ee using the traditional dynamic kinetic resolution of each substrate.